An integrated microcatheter-based dual-analyte sensor system for simultaneous, real-time measurement of propofol and fentanyl - Moonla, Chochanon; Goud, K. Yugender; Teymourian, Hazhir; Tangkuaram, Tanin; Ingrande, Jerry; Suresh, Preetham; Wang, Joseph (Talanta (Oxford), 2020)
According to the American Society of Anesthesiologists Closed Claims Database, one of three drug-related errors is the result administrating an incorrect dose. Directly measuring drug concentration removes the uncertainty in the dose-concentration relationship and addresses inter- and intra-subject variabilities that affect the pharmacokinetics of anesthetics. Here we describe a dual-analyte microcatheter-based electrochemical sensor capable of simultaneous real-time continuous monitoring of fentanyl (FTN) and propofol (PPF) drugs simultaneously in the operating rooms. Such a dual PPF/FTN catheter sensor relies on embedding two different modified carbon paste (CP)-packed working electrodes along with Ag/AgCl microwire reference electrodes within a mm-wide Teflon tube, and uses a square wave voltammetric (SWV) technique. The composition of each working electrode was judiciously tailored to cover the concentration range of interest for each analyte. A polyvinyl chloride (PVC) organic polymer coating on the surface of CP electrode enabled selective and sensitive PPF measurements in μM range. The detection of nM FTN levels was achieved through a multilayered nanostructure-based surface modification protocol, including a CNT-incorporated CP transducer modified by a hybrid of electrodeposited Au nanoparticles and electrochemically reduced graphene oxide (erGO) and a PVC outer membrane. The long-term monitoring capability of the dual sensor was demonstrated in a protein-rich artificial plasma medium. The promising antibiofouling behavior of the catheter-based multiplexed sensor was also illustrated in whole blood samples. The new integrated dual-sensor microcatheter platform holds considerable promise towards real-time, in-vivo detection of the anesthetic drugs, propofol and fentanyl, during surgical procedures towards significantly improved safe delivery of anesthetic drugs. [Display omitted] •Integrated microcatheter-based dual-sensing probe for monitoring of anesthetic drugs.•Real-time, continuous simultaneous in-vivo monitoring of Fentanyl and Propofol in whole blood samples.•Detection of drugs in largely different concentrations without cross talk.•Continuous drugs monitoring during surgical operations towards further medical safety control.